Climate impact of bioH2 production from biogas using CO2 mineralization for carbon capture and storage - Harðardóttir, Hera (SLU/Dept. of Energy and Technology, 2022)
Carbon dioxide (CO2) concentrations in the atmosphere are increasing and are now higher than they have ever been, mostly because of CO2 released from burning fossil fuels for energy. Global energy demand will continue to rise in the future, resulting in increased carbon emissions. Hydrogen (H2) could potentially decarbonize energy systems and replace fossil fuels. Climate impact from H2 production varies but can be considered carbon-neutral if production is replaced with biomethane as feedstock instead of natural gas. Then it is referred to as biogenic hydrogen (bioH2). If carbon capture and storage (CCS) is applied to bioH2 production, it can result in negative emissions. Carbon mineralization is a CCS method where CO2 is injected into underground basaltic reservoirs to rapidly convert into carbonate minerals, providing permanent CO2 storage.